Air in Unexpected Places: Metabolism, Design, and the Making of an 'African' Aircrete. Issue 2 (1st September 2020) - Degani, Michael
Abstract: Aircrete is a lightweight building material with a number of remarkable qualities, including high compression strength, buoyancy and thermal insulation. Perhaps most strikingly, its lack of sand aggregate makes it energy efficient compared to concrete. While aircrete is regularly sold by various construction companies, DIY enthusiasts and technicians around the world are cultivating more home-brew, open-source methods. This article follows James, an American ex-security contractor and mining engineer, as he attempts to convert his own embodied legacies of imperial extraction into a pro-social business venture by designing aircrete machines and mixes for urban Africa. His adventures in aircrete typify an energy future in which an array of intriguing experiments and technologies intersect with a broader entrepreneurial effort to capture Africa's growing consumer markets.